CHALLENGES AND SOLUTIONS IN THE IMPLEMENTATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL IN ISLAMIC RELIGIOUS EDUCATION AT MTS AL-ANWAR AND SMP AL-JIHAD - Siti Ma'rifah; Ahmad Sunoko; Moch. Rizal Fuadiy (Sekolah Tinggi Islam Kendal, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' understanding and practice of Islamic values. However, conventional teaching methods that rely on memorization and lectures often hinder active student engagement. Contextual Teaching and Learning (CTL) is considered a promising model to enhance the effectiveness of PAI by connecting Islamic concepts to real-world experiences. Although CTL has been implemented across various subjects, its application in PAI faces distinct challenges in different educational settings. This study aims to analyze the challenges and solutions of implementing CTL in PAI at two Islamic schools with different backgrounds: MTs Al Anwar (a pesantran/Islamic boarding school) and SMP Al Jihad North Jakarta (a metropolitan Islamic school). A qualitative approach with a comparative case study method was employed, involving interviews, observations, and document analysis. The findings indicate that at the pesantren, the primary challenges are the dominance of rote memorization methods, a lack of case study-based teaching materials, and a lecture-based approach that does not support experiential learning. Meanwhile, at the metropolitan school, the main obstacles include student distractions from social media, a lack of critical thinking skills, and a curriculum that remains exam-oriented. To overcome these barriers, teachers at the pesantren have begun to develop experience-based teaching materials and incorporate more discussions. This study confirms that the successful implementation of CTL in PAI depends on adapting teaching strategies to the specific learning environment. Therefore, a more flexible curriculum, case study-based teaching materials, and teacher training are essential to support experience-based learning.